Development of a Community Wellness Program for Prostate Cancer Survivors. Issue 13 (1st July 2018) - Culos-Reed, Nicole; Dew, Michael; Zahavich, Ashley; Wilson, Kate; Arnason, Tyla; Mackenzie, Michael; Brissette, Christy; Van Patten, Cheri; Santa Mina, Daniel
Abstract : ABSTRACT: Men living with prostate cancer benefit from multidisciplinary wellness programs that include physical activity, nutrition, and stress reduction. Such programs have been shown to decrease treatment-related side effects and reduce the risk of cancer recurrence and other comorbidities associated with prostate cancer, while also improving overall fitness, health, and quality of life. Despite these benefits, access to wellness programs and educational resources for men with prostate cancer are limited in Canada. This study aimed to describe the development of the TrueNTH Lifestyle Management program, an initiative aimed at establishing evidence-based wellness programs in the community to improve access to trained professionals and educational resources specific to the prostate cancer population. Protocol for an integrated, community-based 12-wk intervention of group exercise, yoga, and nutrition education sessions was developed based on evidence and insights from existing cancer-specific programs. Evidence-based tools, resources, and training were developed to support program facilitation and standardize intervention delivery. Pilot testing using the RE-AIM framework was conducted at three distinct community-based sites with demographics, physical fitness, and quality-of-life outcomes collected at baseline and 12 wk. Fifty-eight participants enrolled, with 32 completing quality-of-life measures and 39 completing fitness measures before and after the 12-wk intervention. Significant improvements were seen in the physical measures of body composition, flexibility, dynamic balance, muscular endurance, and functional aerobic endurance as well as weekly moderate and strenuous physical activity levels (all P 's < 0.05). TrueNTH Lifestyle Management provides evidence-based professional training and survivorship resources necessary for the potential implementation of a safe, effective, and beneficial community wellness program for men living with prostate cancer.